Chronic Fatigue Syndrome and DNA Hypomethylation of the Glucocorticoid Receptor Gene Promoter 1F Region: Associations With HPA Axis Hypofunction and Childhood Trauma. Issue 8 (October 2015) - Vangeel, Elise; Van Den Eede, Filip; Hompes, Titia; Izzi, Benedetta; Del Favero, Jurgen; Moorkens, Greta; Lambrechts, Diether; Freson, Kathleen; Claes, Stephan
ABSTRACT: Objectives: Chronic fatigue syndrome (CFS) has been associated with hypothalamic-pituitary-adrenal axis hypofunction and enhanced glucocorticoid receptor (GR) sensitivity. In addition, childhood trauma is considered a major risk factor for the syndrome. This study examines DNA methylation of the GR gene ( NR3C1 ) in CFS and associations with childhood sexual and physical trauma. Methods: Quantification of DNA methylation within the 1F promoter region of NR3C1 was performed in 76 female patients (46 with no/mild and 30 with moderate/severe childhood trauma) and 19 healthy controls by using Sequenom EpiTYPER. Further, we examined the association of NR3C1 -1F promoter methylation with the outcomes of the low-dose (0.5 mg) dexamethasone/corticotropin-releasing factor test in a subset of the study population. Mann-Whitney U tests and Spearman correlations were used for statistical analyses. Results: Overall NR3C1 -1F DNA methylation was lower in patients with CFS than in controls. After cytosine guanine dinucleotide (CpG)-specific analysis, CpG_1.5 remained significant after Bonferroni correction (adjusted p = .0014). Within the CFS group, overall methylation (ρ = 0.477, p = .016) and selective CpG units (CpG_1.5: ρ = 0.538, p = .007; CpG_12.13: ρ = 0.448, p = .025) were positively correlated with salivary cortisol after dexamethasone administration. There was no significant difference in NR3C1 -1F methylation between traumatized and nontraumatized patients. Conclusions: We found evidence of NR3C1 promoter hypomethylation in female patients with CFS and the functional relevance of these differences was consistent with the hypothalamic-pituitary-adrenalaxis hypofunction hypothesis (GR hypersuppression). However, we found no evidence of an additional effect of childhood trauma on CFS via alterations in NR3C1 methylation. Abstract : Supplemental digital content is available in the text.